Hydroponic Planting Training to Maintain Food Security of the People of Bandar Setia Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra - Budi Mulya, Miswar; Nurtjahja, Kiki; Putri, Mimmy Sari Syah (Talenta Publisher, 2023)
The people of Bandar Setia Village experienced the impact of the implementation of PPKM due to regulations delimiting community activities. The limited agricultural land in the village also affects the fulfillment of food needs, especially vegetables. The purpose of this community service is to train the Forum Peduli Sesama Seniman Indonesia Cabang Tembung group representing the community of Bandar Setia in terms of hydroponic farming as an alternative to providing food stocks for the community in the village during the pandemic. The specific target of the training is the hydroponic model that can be made by the people of Bandar Setia village. The method used mixing counseling, training, hands-on practice, and work evaluation. Hydroponics manufacturing uses a mixing of NFT (nutrient film technique) and wick system methods. Vegetables harvested using hydroponics can be used for personal needs or sold according to the needs of the people of Bandar Setia village.